The Prognostic and Clinicopathological Significance of Systemic Immune-Inflammation Index in Bladder Cancer - Li, Jinze; Cao, Dehong; Huang, Yin; Xiong, Qiao; Tan, Daqing; Liu, Liangren; Lin, Tianhai; Wei, Qiang (Frontiers in Immunology, 2022)
Background Systemic immune-inflammation index (SII) has recently emerged as a biomarker for the prognosis of a variety of malignant tumors. However, the role of SII in bladder cancer (BC) remains unclear. To this end, we performed a pooled analysis to investigate the prognostic value of preoperative SII in patients with BC. Methods A comprehensive search of electronic databases (PubMed/Medline, Web of Science, Scopus, and Cochrane Central Register of Controlled Trials) was conducted to determine the eligible studies that were published until January 2022. Pooled hazard ratios (HRs) and odds ratios (ORs) with 95% confidence intervals (CIs) were calculated to evaluate the association between preoperative SII and the prognosis and clinicopathological characteristics of BC. Results Ten studies with 7,087 patients were included in this analysis. SII was observed to be correlated with inferior overall survival (HR = 1.22, 95% CI 1.04–1.44, p = 0.013), cancer-specific survival (HR = 1.68, 95% CI 1.14–2.47, p = 0.009), and recurrence-free survival (HR = 1.29, 95% CI 1.03–1.61, p = 0.027). An increased preoperative SII was also associated with poor tumor differentiation, higher tumor stage, presence of lymph node involvement, and tumor size ≥3 cm (all p < 0.05). Conclusions An elevated preoperative SII is significantly associated with worse survival outcomes and adverse pathological features in patients with BC. Hence, SII may serve as a strong independent prognostic predictor for patients with BC after surgery.